2005
DOI: 10.1074/jbc.m502921200
|View full text |Cite
|
Sign up to set email alerts
|

LIM Kinase 1 Coordinates Microtubule Stability and Actin Polymerization in Human Endothelial Cells

Abstract: Microtubule (MT) destabilization promotes the formation of actin stress fibers and enhances the contractility of cells; however, the mechanism involved in the coordinated regulation of MTs and the actin cytoskeleton is poorly understood. LIM kinase 1 (LIMK1) regulates actin polymerization by phosphorylating the actin depolymerization factor, cofilin. Here we report that LIMK1 is also involved in the MT destabilization. In endothelial cells endogenous LIMK1 co-localizes with MTs and forms a complex with tubulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 40 publications
2
108
1
Order By: Relevance
“…In addition, LIMK1 is concentrated to the microtubules in Wdr1 KO MEF cells and the disassembly of microtubules can partly rescue the phosphorylated Cofilin in these cells. Previous reports show that the PDZ domain is a cytoskeleton binding domain and the PDZ domain can localize LIMK1 to the microtubules (21,37,38). Thus, these results suggest that WDR1 might inhibit the binding of LIMK1 to microtubules and release LIMK1 to the cytoplasm to catalyze Cofilin phosphorylation, therefore regulating the binding of F-actin to Cofilin.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, LIMK1 is concentrated to the microtubules in Wdr1 KO MEF cells and the disassembly of microtubules can partly rescue the phosphorylated Cofilin in these cells. Previous reports show that the PDZ domain is a cytoskeleton binding domain and the PDZ domain can localize LIMK1 to the microtubules (21,37,38). Thus, these results suggest that WDR1 might inhibit the binding of LIMK1 to microtubules and release LIMK1 to the cytoplasm to catalyze Cofilin phosphorylation, therefore regulating the binding of F-actin to Cofilin.…”
Section: Discussionmentioning
confidence: 56%
“…Previous reports showed that LIMK1 activity was inhibited by binding with BMP-RII (bone morphogenetic proteins receptor II) or microtubules (21,37,38). Because the LIMK1 antibody did not work well for immunostaining, LIMK1 with the Myc tag was overexpressed in control and Wdr1 KO MEF cells to examine whether WDR1 regulates LIMK1 by changing its localization.…”
Section: Wdr1 Regulates Phosphorylation Of Cofilin In a Dose-independmentioning
confidence: 99%
“…Another major challenge is to identify the mechanisms that couple the actin-dependent fission mechanisms described here with our recent observation that kinesin 5B is essential for generation and transport of p75 carrier vesicles from Golgi to PM (Jaulin et al, 2007). In this regard, it is interesting to mention a recent report that postulates a role for LIMK1 in coordinating MT and actin cytoskeleton function (Gorovoy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) of how LIMK2 regulates microtubule-targeted drug action is not yet known. Earlier studies have shown that LIMK1 regulates microtubule stability (Gorovoy et al, 2005) through phosphorylation of p25 also known as tubulin polymerization promoting protein (Acevedo et al, 2007). Phosphorylation of p25 by LIMK1 inhibits its ability to polymerize tubulin resulting in microtubule disassembly.…”
Section: Discussionmentioning
confidence: 99%